Profitabilitas, Likuiditas, Leverage dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Didha Putri Citradika; Tiara Setyo Pangestu; Meliza Meliza (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Firm value represents a measure of management success in managing corporate funds and serves as a reference for investors in assessing investment feasibility. Recent conditions indicate that several companies in the property and real estate sector face challenges that may potentially lead to financial losses. This study aims to examine and analyze the effect of profitability, measured by Return on Assets (ROA), liquidity, measured by the Current Ratio (CR), leverage, measured by the Debt to Equity Ratio (DER), and investment decisions, measured by the Price Earnings Ratio (PER), on firm value, measured by the Price to Book Value (PBV). This study employed a quantitative research approach using secondary data obtained from financial statements published by the Indonesia Stock Exchange. The population of this study consisted of property and real estate companies from 2022 to 2024. The sample was selected using a purposive sampling technique, resulting in 242 observations. The data were analyzed using multiple linear regression with SPSS version 20. The results show that profitability (ROA) has a positive and significant effect on firm value (PBV). Liquidity (CR) has a negative and insignificant effect on firm value (PBV). Leverage (DER) has a positive and significant effect on firm value (PBV). Investment decisions (PER) also have a positive and significant effect on firm value (PBV).